Preannouncing competitive decisions in oligopoly markets - Corona, Carlos; Nan, Lin (Journal of Accounting and Economics, 2013)
We examine a duopolistic setting in which firms can preannounce their future competitive decisions before they actually implement them. We show that there is a unique equilibrium in which both firms preannounce and overstate their future actions when uncertainty of demand is low. We find that firms choose higher real actions than the ones they would choose in the absence of preannouncements. Moreover, the real actions of both firms are single-peaked functions of their credibility. In a Cournot market, firms face a prisoner's dilemma in which preannouncing lowers firms' profits. If firms could commit not to preannounce, they would remain silent. In a Bertrand market, firms overstate their future actions to foster collusion.